Magnetic responsive composites made from a sulfur-rich polymer. Issue 39 (21st September 2022) - Lundquist, Nicholas A.; Yin, Yanting; Mann, Maximilian; Tonkin, Samuel J.; Slattery, Ashley D.; Andersson, Gunther G.; Gibson, Christopher T.; Chalker, Justin M.
Abstract : A magnetic responsive composite was made from a sulfur-rich polymer and iron nanoparticles. Diverse applications in mercury remediation, microwave curing, and magnetic responsive actuators were demonstrated. Abstract : A composite was prepared by hot-pressing a polysulfide polymer in the presence of γ-Fe2 O3 nanoparticles. The polymer was prepared by the direct copolymerisation of elemental sulfur and canola oil and the hot-pressing embedded the magnetic particles in the polymer. The resulting composite was used as a mercury sorbent capable of magnetic retrieval, and the magnetic particles allowed rapid microwave heating for curing into a consolidated object that could be remotely manipulated with a magnet. The multi-functional nature of the magnetic-responsive composite portends new frontiers for sulfur-rich polymers in environmental protection, recyclable materials, and magnetically activated machine components.